Concise Asymmetric Synthesis of Kweichowenol A - Konrad, David B.; Kicin, Bilal; Trauner, Dirk (Synlett, 2019)
An asymmetric 11-step synthesis of the polyoxygenated cyclohexene natural product kweichowenol A from the traditional Chinese medicinal herb Uvaria kweichowesis is reported. The oxygenation pattern was installed on a linear precursor by exploiting the acyclic stereocontrol of the Kiyooka aldol reaction, as well as Cram chelate-controlled Grignard reactions. Ring-closing metathesis and a selective benzoylation then gave the natural product.
Keywords: kweichowenol A; Kiyooka aldol; asymmetric synthesis; natural product synthesis; acyclic stereocontrol